Analysis of Micro Hydro Potential as A New Renewable Energy Source: (Case Study: Bangkong Waterfall, Kuningan Regency, Indonesia) - Nurmansyah, Agus; Alkaf, Muhammad; Aulia, Nahdiyah ‘Afni; Nurdiyanto, Nurdiyanto (Riviera Publishing, 2024)
Electricity demand in Indonesia is currently increasing along with population growth, economic growth, and development. This increase can lead to an energy crisis if it is not accompanied by the provision of additional power plants. This study aims to analyze the micro-hydro potential located at Bangkong Waterfall, Kuningan Regency. The research uses a quantitative approach that begins with field surveys and data collection from relevant agencies. Next, the dependable discharge analysis uses the Thiessen polygon method based on rainfall data and watershed area, as well as flow discharge analysis using the rational method. The results of calculations using the Thiessen polygon method and the rational method yield Q80 with a minimum discharge of 0.009 m³/d and a maximum discharge of 1.160 m³/d. For direct discharge analysis, the Float method is used to calibrate the calculation results with field conditions. The direct discharge analysis using the Float method yields 0.32 m³/d. Based on the efficiency considerations of the micro-hydro power plant (MHPP) components such as a head of 20 meters, turbine type efficiency, water density, gravity factor, and flow discharge in the pipe of 0.109 m³/d, the potential power that can be generated at the Bangkong Waterfall micro-hydro power plant is 16,097.23 Watts or 16.097 Kilowatts.